Critical Political Theory : Interrogating Contemporary Politics - Oliver Flügel-Martinsen (transcript, 2025)
How can political theory strengthen democracy and emancipatory social change while remaining critical of its own norms and foundations? How can it confront populist movements that claim to defend democracy but in fact advance authoritarian agendas? Oliver Flügel-Martinsen engages with key thinkers of the political – among them M. Foucault, J. Derrida, C. Lefort, C. Mouffe, I. M. Young, J. Rancière, W. Brown, R. Geuss, A. Mbembe, and J. Butler – to address these challenges. Revisiting truth-skeptical approaches, neoliberal hegemony, exclusions in the name of an essentialist understanding of the people, and global injustices, he explores how critical theory can help us escape the present in working toward a different future.